Optimal Management for Primary High Grade Ta Bladder Cancer: Role of re‐staging TURBT and Intravesical Adjuvant Therapy - Tarek Ajami; Sunwoo Han; Ruben Blachman‐Braun; Helen Y. Hougen; Yuval Avda; Mark L. Gonzalgo; Bruno Nahar; Sanoj Punnen; Dipen J. Parekh; Isildinha M. Reis; Chad R. Ritch (BJUI Compass)
Abstract Objective This study aims to investigate the impact of risk group classification, restaging transurethral resection (re‐TURBT), and adjuvant treatment intensity on recurrence and progression risks in high‐grade Ta tumours in patients with non‐muscle invasive bladder cancer (NMIBC). Materials and methods Data from a comprehensive bladder cancer database were utilized for this study. Patients with primary high‐grade Ta tumours were included. Risk groups were classified according to AUA/SUO criteria. Tumour characteristics and patient demographics were analysed using descriptive statistics. Cox proportional hazard regression models were used to assess the effect of re‐TURBT and other clinical/treatment‐related predictors on recurrence‐ and progression‐free survivals. The survivals by selected predictors were estimated using Kaplan–Meier method, and groups were compared by the log‐rank test. Results Among 218 patients with high‐grade Ta bladder cancer, those who underwent re‐TURBT had significantly better 5‐year recurrence‐free survival (71.1% vs. 26.8%, p = 0.0009) and progression‐free survival (98.6% vs. 73%, p = 0.0018) compared with those with initial TURBT alone. Full BCG treatment (induction and maintenance) showed lower recurrence risk, especially in high‐risk patients. However, residual disease at re‐TURBT did not significantly affect recurrence risk. Conclusions This study highlights the significance of risk group classification, the role of re‐TURBT, and the intensity of adjuvant treatment in the management of high‐grade Ta tumours. A risk‐adapted model is crucial to reduce the burden of unnecessary intravesical treatment and endoscopic procedures.